Mindfulness For Dummies, 3rd Edition - Alidina, Shamash (For Dummies, 2020)
Breathe deep, declutter your mind, and start leading a healthier, happier life The worry won't stop. You're feeling stressed out, the day-to-day seems overwhelming, and it seems difficult to do the simplest things. How can you escape this continual negative feedback loop? Mindfulness is the answer. Practiced by millions of people worldwide, mindfulness puts you back in a healthy relationship with yourself by teaching techniques that allow you to maintain a moment-by-moment awareness of your thoughts, feelings, and environment. Clear your mind of distracting thoughts Focus on breathing and other self-control techniques Change the wiring and makeup of your brain Free yourself from the stress With this expert, easy-to-follow guide, there's never been a better time to get to grips with mindfulness and the many ways it can help you lead a happier, healthier life.
Online resource; Title from title page (viewed February 5, 2020)